(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Characteristic of every developing nation, Kenya has found itself at crossroads; defining the banking industry with the urgeto provide banking services to majority of the unbanked populations. Mobile banking is a banking model that has beenadopted by Kenyan Banks to reach out to unbanked populations. This paper is based on a case study conducted in Kenyaon selected mobile banking products in 2012. The Actor Network theory methodology was used to identify and followactors. Using in-depth interviews with key informants, survey of users and agents as well as focus group discussions andobservation, it was established that agent phones and Point of service (POS) devises were used to deliver traditionalbanking services to users whose access mode was their mobile phone or debit cards. There existed partnerships betweenbanks and mobile network operators whose operations were regulated by the Central Bank of Kenya and theCommunications Authority of Kenya. This paper seeks to explore fundamental requirements for the interplay of actors inthe execution of mobile banking services. It critically analyses data collected, with reference to the Network Society theoryby Manuel Castells and Actor Network theory by Michael Callon and Bruno Latour, to inform on cross-sectoral partnerships and user attributes necessary in mobile banking uptake and use.